Does digitalization boost companies’ outward foreign direct investment? - Peng, Cheng; Yang, Shanshan; Jiang, Hui (Frontiers in Psychology, 2022)
The development of digital economy influences the digital transformation of companies while profoundly affecting the production efficiency, business model and overall strategy of firms, which has an important impact on business decisions, including foreign investment decisions. However, whether and how digitalization affects corporate OFDI has not been sufficiently empirically investigated. Taking Chinese listed companies in Shanghai and Shenzhen A-shares from 2009 to 2020 as samples, this paper constructs corporate digitalization indicators by using "text analysis method" and empirically tests the impact of digitalization on corporate OFDI and its path. The study finds that digitalization significantly promotes corporate OFDI. In terms of the influential mechanism, digitalization promotes corporate OFDI by improving total factor productivity and reducing financing constraints. In addition, external digital economy policies can provide favorable support for the digital transformation of firms. Meanwhile, the impact of digitalization on corporate OFDI is somewhat heterogeneous due to the different resource utilization efficiency and market environment. This study not only reveals the impact mechanism of digitalization on corporate OFDI, but also provides micro evidence for the deep integration of digital economy and real economy. Meanwhile, the findings have important implications for the formulation and implementation of digital policies.